CONSTRUCTION AND PERFORMANCE EVALUATION OF AN INTEGRATED SOLAR COOKING AND DRYING SYSTEM - Jibrin, Inuwa; Garba, M. M.; Argungu, G. M.; Mohammed, M. L.; Anas, Usman (FUDMA JOURNAL OF SCIENCES, 2023)
An integrated solar cooking and solar drying system was developed using locally available materials. The system performs both functions of cooking and drying simultaneously. Performance evaluation of the system was carried out using tomatoes for drying; while rice, beans and eggs were used to carryout cooking experiment. For the purpose of performance evaluation, total global radiation, ambient temperature, humidity, water temperature were monitored, taken and recorded. Results obtained from the system and that of the non-integrated systems were compared using excel as a statistical tool for analysis to ascertain the performance of the integrated system. The average temperatures recorded in the integrated system during drying were 45.3, 46.0 and 45.9, while that of the non-integrated system were 40.2, 39.9 and 39.7. The average temperatures recorded during cooking of egg, beans and rice using the integrated system were 83.1, 83.4 and 78.2, while that of the non-integrated system were 68.8, 86.3 and 65.0. This indicates higher heat generation and faster drying and cooking rates in the integrated system than the non-integrated system. The system has a total cost estimate of N30,600 with an added advantage of cooking and drying simultaneously. It is portable and can help in improving the ambient air quality. Furthermore, the integrated system will occupy less space and gives higher efficiency compared to the conventional single use systems.